2014
DOI: 10.1177/1468087414564229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of rail pressure and biodiesel fueling on the particulate morphology and soot nanostructures from a common-rail turbocharged direct injection diesel engine

Abstract: An investigation of the impact of rail pressure and biodiesel fueling on exhaust particulate agglomerate morphology and primary particle (soot) nanostructure was conducted with a common-rail turbocharged direct injection diesel engine. The engine was operated at steady state on a dynamometer running at moderate speed with both low (30%) and medium-high (60%) fixed loads, and exhaust particulate was sampled for analysis. The fuels used were ultra-low sulfur diesel and its 20% v/v blends with soybean methyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 60 publications
(114 reference statements)
2
27
0
Order By: Relevance
“…Vander Wal and Tomasek (2004) and Hurt et al (2000) reported that the residence time, combustion temperature and soot precursor mass determine the nanostructure. However, Ye et al (2016) observed similar particulate nanostructure at different engine loads and different fuel injection pressures. They suggested that at high fuel injection pressures, higher combustion temperatures lead to a more ordered nanostructure, but the shorter residence time for soot formation contributes to a disordered nanostructure.…”
Section: Particulate Nanostructurementioning
confidence: 83%
See 4 more Smart Citations
“…Vander Wal and Tomasek (2004) and Hurt et al (2000) reported that the residence time, combustion temperature and soot precursor mass determine the nanostructure. However, Ye et al (2016) observed similar particulate nanostructure at different engine loads and different fuel injection pressures. They suggested that at high fuel injection pressures, higher combustion temperatures lead to a more ordered nanostructure, but the shorter residence time for soot formation contributes to a disordered nanostructure.…”
Section: Particulate Nanostructurementioning
confidence: 83%
“…Salamanca et al (2012a) found insignificant difference in the mean primary particle diameters between diesel particles and biodiesel particles and the average diameter is 22 nm. Ye et al (2016) reported that the mean diameter of primary particles from B20 is around 30 nm which is 35-40% higher than that from diesel. Different results may be attributed to the different diesel engines and testing conditions used in the investigations (Ye et al 2016).…”
Section: Primary Particle Sizementioning
confidence: 97%
See 3 more Smart Citations